TECHNICAL AND ECONOMICAL FEASIBILITY ANALYSIS APPLIED TO HEALTH:: SCHOOL-CLINIC IMPLANTATION PROJECT - Costa, Heirislane Macedo; SANTOS, JULIO CESAR DOS; Freitas, Patrícia Martins (REVISE - Revista Integrativa em Inovações Tecnológicas nas Ciências da Saúde, 2021)
The importance of the school-clinic to psychology course is associated to teaching, researching and extension affairs in public universities in Brazil. Considering the actual context in Santo Antônio city, Bahia, in which is located the psychology course (Centro de Ciências da Saúde - Health Sciences Center - UFRB), it´s possible to realize that the institutions that actually assist mental health don´t have the necessary basic structure to the course´s academic needs. These limitations can make the clinical formation harder, restricting probation vacancies. The objective of the present study is to demonstrate the processes of economic and technical viability analysis applied in health. The used methodology was the study of economic and technical feasibility. The analysis object was the project of construction of a psychology school-clinic construction in the Universidad Federal do Recôncavo da Bahia (UFRB). These results can contribute to increase other feasibility studies of the health care area. The economy instruments usage for health care can reduce the failure of many public and private enterprises. Keywords: School-Clinic, Economic Feasibility, Saúde-Mental.